Characteristics and Risk Factors for Polycystic Ovarian Syndrome Among Females - Muhammad, Bakhtyar Kamal (Kurdistan Journal of Applied Research, 2020)
Polycystic ovary syndrome (PCOS) is a major endocrinal syndrome may affect the female at adult ages. In polycystic ovary, the ovarian seen that are enlarged and the investigation may base on ultra-sonographic detection. Polycystic ovarian syndrome always represents a spectrum of syndrome rather than the diseases. Also clinically presented by polycystic on ovarian and generally demonstrated by reversible. 104 female patients were examined, 18 (17.3%) of females were diagnosed with polycystic ovarian syndrome. The mean age was 24.62 ± 7.32 years (ranged from 15 month to 50 years-old). 17 (94.4%) of women were less than 25 years-old p-value=0.03, hormonal abnormality was the most frequent symptoms in relation to polycystic ovarian syndrome 10 (55.5%) and p-value=0.001. 16 (88.9%) of women experienced vaginal discharge p-value=0.09. In conclusion, one from six females is expected to experience polycystic ovarian syndrome. Young females are probably to be at a high risk for developing polycystic ovarian syndrome. Despite uncertain etiology of polycystic ovarian syndrome, marital status, stress or anxiety, doing a regular exercise and pregnancy are all related parameters to the incidence of polycystic ovarian syndrome. Additionally, Cases with high hormonal abnormality and vaginal excretion could be considerable indicators of polycystic ovarian syndrome.